Groeten uit de hemel: Voorbij het theologisch ongemak met levenstekens van dierbare overledenen? - Korte, Anne-Marie (Tijdschrift voor theologie, 2011)
One in six of the more than 2500 contemporary miracle stories that the Dutch Catholic Broadcasting Corporation (KRO) collected between 2002 and 2007 for a television programme entitled Wonderen bestaan! [Miracles Do Happen!], is about experiencing signs of life from the beloved deceased. Despite theology’s growing interest for experiential narratives, there is practically no theological research on this type of story. This article explores theology’s discomfort with this type of story. That unease appears to relate to the fact that the Christian tradition has not cultivated contact with the beloved deceased. Yet it seems even more strongly related to the inner tensions in Christian doctrine and Christian imagery of life after death, which our modern, rational individualistic culture has intensified. Starting out from initial work in this field by William James and Andrew Greeley, this article examines several established assumptions and aporia in the research theology and religious sciences have done into the experience of contact with the departed. It then presents a systematic review of the KRO’s miracle stories about signs of life from the deceased. The article argues that these modern miracle stories are indicative of the shifting and new forms according to which death and mourning are currently experienced and interpreted. These stories interrogate the modern, rigid separation between life and death and call in question the opposition between religious and secular frames of reference. These stories can be considered as creative sacralisation of life-despite-death; most are, not by chance, told by women acting the role of mediators between life and death and as those that maintain the ties, factual and symbolic, between persons on both sides. The use of the miracle story as literary genre makes it possible that the beloved departed are not merely remembered and made present but that they also appear as living persons that initiate contact and strengthen ties over the frontiers of death.